BOOK AWARDS OF BOOKS FOR CHILDREN AND YOUTH 2017/2018 - Malý, Radek (Bohemica Olomucensia, 2020)
The paper presents Czech awards focused on books for children and young people: Magnesia Litera, The Most Beautiful Book of the Year, Suk - we all read and more. It also collects and comments on individual titles. The research is focused on the period 2017/2018.
Keywords: childern book; book award; contemporary Czech literature